The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3109/03008207.2014.951440
|View full text |Cite
|
Sign up to set email alerts
|

COMP does not directly modify the expression of genes involved in cartilage homeostasis in contrast to several other cartilage matrix proteins

Abstract: In contrast to collagen II and matrilin-3, COMP lacks the ability to trigger a proinflammatory response in chondrocytes, although it carries an RGD motif and can bind to integrins. COMP is a well-accepted biomarker for osteoarthritis but increased COMP levels do not necessarily correlate with inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The inflammatory potential of marathon running as previously shown (Nickel, Emslander, et al, 2012) may influence tissue metabolism and may hence be an important factor for long-term effects of marathon running. Because COMP lacks the ability to trigger a proinflammatory response in chondrocytes (Ruthard et al, 2014), increased serum COMP in slower runners may rather result from than cause the greater release of hsCRP in these participants. We included only runners without any preclinical inflammation.…”
Section: Marathon Finishing Time Pro-inflammatory and Cartilage Biommentioning
confidence: 99%
“…The inflammatory potential of marathon running as previously shown (Nickel, Emslander, et al, 2012) may influence tissue metabolism and may hence be an important factor for long-term effects of marathon running. Because COMP lacks the ability to trigger a proinflammatory response in chondrocytes (Ruthard et al, 2014), increased serum COMP in slower runners may rather result from than cause the greater release of hsCRP in these participants. We included only runners without any preclinical inflammation.…”
Section: Marathon Finishing Time Pro-inflammatory and Cartilage Biommentioning
confidence: 99%
“…Treatment of primary human chondrocytes with fragments of collagen II as well as the collagen associated protein matrilin-3 induced a concentration- and time-dependent release of interleukin (IL)-1, -6, -8, TNFα and MMP-1, -3, -13 [ 80 ]. Interestingly, larger fragments of COMP have not been able to do so in identical in vitro experiments [ 81 ]. Very recently, the effect of smaller COMP-derived peptides that have been detected in the degenerated cartilage tissue of OA patients was studied in different in vitro assays.…”
Section: The Role Of Proteases and Cytokines In Oamentioning
confidence: 99%
“…The 3 peptides reported originate from the multifunctional C-terminal domain of COMP, which plays diverse roles in cartilage homeostasis, 11 inflammation, 12 and transforming growth factor-β (TGF-β) signaling. 13 , 14 Previous research found that full-length COMP was unable to modify the expression of proinflammatory markers in cartilage, 15 unlike its binding partner MATN3 and its fragments. 16 However, we hypothesized that those COMP fragments released by cartilage could have an OA-relevant biological function.…”
Section: Introductionmentioning
confidence: 99%